Does the format of the adult ADHD self-report scale influence screen-positive rates? A randomized controlled trial in primary care - Kraut, Roni Y.; Ono, Christian; Garrison, Scott; Kamal, Omar; Doroshuk, Marissa L.; Vandermeer, Ben; Amanna, Gerard; Babenko, Oksana (Frontiers in Psychiatry, 2026)
ObjectiveThe Adult Attention-Deficit-Hyperactivity-Disorder (ADHD) Self-Report Scale (ASRS) is widely used for ADHD screening in primary care clinics worldwide. While it offers a quick and efficient method to screen for ADHD, it also has a high false positive rate. The standard ASRS format—shaded responses for screen-positive items and grouping the key questions in Part A—may contribute to this issue. The objective of this study is to examine whether these design features impact the screen positive rate.MethodsThis is a 2x2 factorial randomized controlled trial that ran from July to October 2024. Individuals 19 to 65 years old attending a family medicine clinic received at random one of four ASRS forms on registration (standard, grouping only, shading only, and no shading and no grouping). Logistic regression was used to analyze the results.ResultsA total of 595 participants completed the study: mean age 39 (standard deviation 12), 79% women, 85% with at least some post-secondary education, 54% White, 33% Asian, 13% other ethnicities. Additionally, 14% had a prior ADHD diagnosis, and 23% suspected they had undiagnosed ADHD. Overall, 32% of participants screened positive for ADHD, and grouping and shading were not statistically significant predictors of a positive ADHD screen (Odds ratio [OR] 1.25, 95% CI 0.98–1.58 and OR 0.88 95% CI 0.69–1.12 respectively). In contrast, prior ADHD diagnosis and suspected undiagnosed ADHD were statistically significant predictors (OR 47.4, 95% CI 23,1–97.0 and OR 16.2, 95% CI 9.7–27.2, respectively).ConclusionThe standard ASRS does not appear to increase the screen positive rate. Nevertheless, the high positive screening rate highlights the need for more effective ADHD screening tools in primary care.Clinical trial registrationClinicaltrials.gov, identifier NCT06530758.